PERSEPSI MAHASISWA TENTANG NILAI-NILAI ETIKA DALAM PENYAJIAN PELAPORAN KEUANGAN PERUSAHAAN YANG BERTANGGUNG JAWAB - Hotman Tohir Pohan (Media Ekonomi, 2012)
The aim of this research to know the perception of students about ethics values in professional code of ethic and business ethics. The analysis is based on the answer from responden where its data are gathered from accounting students and business students of economic faculty Trisakti University. The questioners about ethical concept is took from code of ethic management accountant or internal accountant that is Competence, Confidentiality, Honesty, Objectivity, Accountability and Responsibility. Result showed that, first there are not significantly perception different between accounting students and bussines student about ethical concept of competence, objectivity, and accountability ,but there are significantly perception different between accounting students and bussines students about ethical concept confidentiallity and honesty. Secondly there are not significantly perception different between students after took subject code of ethic and students before took subject code of ethic. Thirdly, there are not significantly perception different between gender of students about code of ethic and bussines ethics.Keywords: Perception, Ethical Values, Code of Ethic, Preparation and Presentation of Financial Statement.